Hubungan daya ledak otot tungkai dengan kemampuan tendangan sabit Pencak Silat pada Perguruan PSHT di Kota Lubuk Linggau - Eci Oktarina; Helvi Darsi; Muhammad Supriyadi (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
This study aims to see a picture of how big the relationship between the explosive power of the limb muscles and the ability to kick the sickle of Pencak Silat at PSHT College in Lubuklinggau City. Quantitative research methods. Data collection techniques in the study used observation and treatment tests. The data analysis technique used in this study is the normality test, product moment correlation test and hypothesis testing. between Limb Muscle Explosion with Sickle Kick Speed, and this figure belongs to the category of very strong correlation. The results of the coefficient of determination of 0.616 can be explained that the contribution between Explosive Power of the Limb Muscles and the Speed ​​of Sickle Kicks is 61.6%, the remaining 38.4% is explained by other factors. Fcount of 14.089 with a significance of 0.001, it can be concluded that H0 is rejected, which means that there is a significant relationship between the Explosive Power of the Limb Muscle and the Speed ​​of the Sickle Kick.